Assessment of USDA Conservation Reserve ProgramState Acres for Wildlife Enhancement (CRP SAFE) - Johnson, Alexandra K.; Kleintjes Neff, Paula K. (My University, 2017)
State Acres for Wildlife Enhancement (SAFE) is one of many Conservation Reserve Programs (CRP) administered by the United States Department of Agriculture (USDA) Farm State Agency (FSA). SAFE emphasizes conservation practices that will enhance and manage habitat to benefit threatened, endangered and other high-priority wildlife species. Eligible landowners voluntarily establish and maintain vegetation cover on their once highly erodible cropland for 10 or 15-year contracts. In turn, they receive annual rental payments from the FSA and cost-share for seeding, maintenance and technical assistance from the USDA Natural Resource Conservation Service (NRCS). Several studies have analyzed the benefits of Farm Bill conservation programs for wildlife but this is the first study of its kind to evaluate the status, coverage and effectiveness of SAFE CRP in Wisconsin. Currently, there are more than 1 million acres enrolled in SAFE nationwide, with up to 13,750 acres distributed among five Wisconsin SAFES across 17 counties.
Color poster with text, maps, and graphs
Keywords: Conservation Reserve Program (U.S.); Endangered species; Wildlife conservation; Posters